2017
DOI: 10.1111/eva.12526
|View full text |Cite
|
Sign up to set email alerts
|

Slow and temperature‐mediated pathogen adaptation to a nonspecific fungicide in agricultural ecosystem

Abstract: The spread of antimicrobial resistance and global change in air temperature represent two major phenomena that are exerting a disastrous impact on natural and social issues but investigation of the interaction between these phenomena in an evolutionary context is limited. In this study, a statistical genetic approach was used to investigate the evolution of antimicrobial resistance in agricultural ecosystem and its association with local air temperature, precipitation, and UV radiation. We found no resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 79 publications
(121 reference statements)
4
26
0
1
Order By: Relevance
“…Our result suggests that elevated air temperature associated with global warming in the future may increase the effectiveness of the fungicide. This result also supports the hypothesis that temperature can regulate both pathogen sensitivity to fungicides and the toxicity of chemical compounds [25,27]. The result further showed that an increase in fungicide doses could leads to a decrease in sensitivity among the pathogens (Figure 4).…”
Section: Impact Of Elevated Temperature and Global Warming On Efficacsupporting
confidence: 85%
See 2 more Smart Citations
“…Our result suggests that elevated air temperature associated with global warming in the future may increase the effectiveness of the fungicide. This result also supports the hypothesis that temperature can regulate both pathogen sensitivity to fungicides and the toxicity of chemical compounds [25,27]. The result further showed that an increase in fungicide doses could leads to a decrease in sensitivity among the pathogens (Figure 4).…”
Section: Impact Of Elevated Temperature and Global Warming On Efficacsupporting
confidence: 85%
“…No pairwise correlation between Q ST and F ST across the populations and significantly higher overall Q ST than overall F ST is an indication that evolution of azoxystrobin resistance was under diversifying selection driven by local adaptation. This type of selection can only be possible when some of the phenotypic traits are favored by local environments such as climatic conditions or agricultural practices [58], for example, the density of fungicide application or trade-offs associated with fungicide resistant mutants [27,59]. Previous studies demonstrated that Q ST -F ST comparisons are a powerful approach to infer the importance of diversifying selection in the evolution of quantitative traits [44,60], and revealed that the evolutionary mechanism serves as main driver for the development of fungicide resistance and other ecological traits in pathogen populations including virulence, pesticide resistance, and temperature tolerance in Puccinia striiformis, Mycosphaerella graminicola, P. infestans, and Parastagonospora nodorum, [38,45,61,62].…”
Section: Sources Of Genetic Variation Contributing To Azoxystrobin Admentioning
confidence: 99%
See 1 more Smart Citation
“…Arrows represent the transfer of isolates to fresh rye B plates after 10 days (one generation), and orange circles indicate the stages when aggressiveness of acclimated isolates was tested. The acclimation lasted for 20 generations (transfers) with 10 days in each generation as described previously (He et al, 2018;Yang et al, 2016;Zhan & McDonald, 2011). Association between colony size and aggressiveness in both the acclimated and unacclimated parental isolates was evaluated by Pearson's correlation (Lawrence & Lin, 1989).…”
Section: Colony Growth and Aggressiveness Measurement Of Acclimatedmentioning
confidence: 99%
“…In addition, A. alternata has a broad host range including many grasses. A continuous influx of sensitive isolates from other wild hosts which are usually not exposed to the fungicides is likely to dilute selective pressures and prevent the buildup of resistance level in potato populations of A. alternata [32].…”
Section: Sequestration Of the Antifungal Agents In Cell Membranes Andmentioning
confidence: 99%